Suspect and non-target screening of ovarian follicular fluid and serum – identification of anthropogenic chemicals and investigation of their association to fertility. Issue 10 (28th September 2021) - Hallberg, Ida; Plassmann, Merle; Olovsson, Matts; Holte, Jan; Damdimopoulou, Pauliina; Sjunnesson, Ylva C. B.; Benskin, Jonathan P.; Persson, Sara
Abstract : This work shows the applicability of non-target screening for prioritizing environmental contaminants in the ovarian follicular fluid, identifying both substances associated to embryo quality and with high calculated hazard to humans. Abstract : In this work, ultra-high performance liquid chromatography-high resolution (Orbitrap) mass spectrometry-based suspect and non-target screening was applied to follicular fluid ( n = 161) and serum ( n = 116) from women undergoing in vitro fertilization in order to identify substances that may be associated with decreased fertility. Detected features were prioritized for identification based on (i) hazard/exposure scores in a database of chemicals on the Swedish market and an in-house database on per- and polyfluoroalkyl substances (PFAS); (ii) enrichment in follicular fluid relative to serum; and (iii) association with treatment outcomes. Non-target screening detected 20 644 features in follicular fluid and 13 740 in serum. Two hundred and sixty-two features accumulated in follicular fluid (follicular fluid: serum ratio >20) and another 252 features were associated with embryo quality. Standards were used to confirm the identities of 21 compounds, including 11 PFAS. 6-Hydroxyindole was associated with lower embryo quality and 4-aminophenol was associated with higher embryo quality. Overall, we show the complexity of follicular fluid and the applicability of suspect and non-target screening for discovering both anthropogenic and endogenous substances, which may play a role in fertility in women.